Penerapan Tools Value Stream Mapping dan Kaizen untuk Meningkatkan Process Cycle Efficiency pada PT.XYZ - Nando, Fiky Two; Bosco, Evan Milando; Putri Farenzy, Fani Nafianti; Fadhilah, Rizqy Kautsar; Anam, Khoirul (Indonesian Journal of Engineering and Technological Innovation, 2025)
An efficient production process requires reducing non-value-added activities and minimizing waste at every stage of the work process. However, in practice, the production process at PT. XYZ still exhibits several forms of inefficiency, such as high waiting times, excessive material movement, disorganized work areas, and the emergence of defective products due to a lack of standardized machine settings. This study aims to identify sources of waste and improve production process efficiency through the application of Lean Manufacturing methods using Value Stream Mapping (VSM), Process Activity Mapping (PAM), and the Kaizen and 5S approaches. The results of the Current State Value Stream Mapping (CMS) mapping indicate that value-added activities only contribute 54.64% of the total process time, while non-value-added and necessary but non-value-added activities still dominate the workflow. Furthermore, the results of the waste questionnaire indicate that the largest waste occurs in waiting, followed by defects and transportation. Through the PAM analysis, operations are found to be the most dominant activity, but delays and transportation activities still significantly impact overall process time. Improvement efforts were implemented by formulating Kaizen actions, including developing machine SOPs, optimizing layouts, implementing FIFO for materials, strengthening visual control, and gradually implementing 5S. The implementation of these improvement methods has been proven to reduce the duration of non-value-added activities and improve the overall production flow. Thus, the combination of VSM, PAM, and Kaizen is effective in identifying root causes, reducing waste, and increasing production process efficiency at PT. XYZ.